Development Of Formulation and Technology of Combined Generic Powder for Oral Solution in Sachets Based on the Quality by Design Approach (Global Journal of Medical Research, 2022)
Using Quality by design approaches dispersion analysis and random balance method the formulation and technology of powder for oral solution in sachets which includes paracetamol ascorbic acid phenylephrine hydrochloride and pheniramine maleate have been developed The influence of 27 excipients from 5 functional groups on 11 quality attributes was studied by the dispersion analysis The preferred excipients were selected using the utility function
Keywords: chemistry; pharmaceutical; drug development; powders; drugs; generic; risk assessment; quality indicators